Influence Of Accounting Information Systems, Control Internal And Work Motivation On Performance Employees At PT. Selalu Cinta Indonesia - Rozza Sugmawati; Bagus Kusuma Ardi; Batista Sufa Kefi (International Forum of Researchers and Lecturers, 2025)
The purpose of this research is to determine the influence of accounting information systems, internal control systems and work motivation on employee performance at PT. Selalu Cinta Indonesia. The research location is at PT. Selalu Cinta Indonesia Semarang. Analysis tools use data reduction, presenting data, and verifying conclusions. The analysis method used is multiple linear regression. Hypothesis testing uses a 5% degree of freedom. The results of the reliability and validity tests show that all question items are reliable and the constructs are valid, besides that the regression meets the model fit. The research results showed that the Accounting Information System (X1) had a significant positive effect on employee performance (Y). Internal Control (X2) has a significant positive effect on employee performance (Y). Work motivation (X3) has a significant positive effect on employee performance (Y).